Co2TA0.5 monatomic catalytic material for efficiently degrading sulfamethoxazole and preparation method of Co2TA0.5 monatomic catalytic material
The activation of potassium hydrogen sulfate through Co2TA0.5 single-atom catalyst solves the problem that traditional wastewater treatment is difficult to remove SMX, realizes the efficient degradation of SMX and the reusable catalyst, and is suitable for various water environments.
Patent Information
- Application Number
- CN202411332598.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional sewage treatment processes have difficulty completely removing sulfamethoxazole (SMX), causing it to accumulate in the water environment, contaminate ecosystems and negatively affect microorganisms and aquatic plants.
The Co2TA0.5 single-atom catalyst is used to efficiently degrade SMX by activating potassium permonosulfate. It has a wide pH application range and anti-interference ability, and can quickly degrade SMX at room temperature.
100% degradation of SMX is achieved, maintaining the catalytic performance good at different temperatures and water conditions, and the catalyst is reusable, reducing cost and environmental impact.
Smart Images

Figure CN119215898A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of single-atom catalyst activated persulfate, and in particular relates to a Co2TA catalyst capable of efficiently catalyzing the degradation of sulfamethoxazole. 0.5 Single atom catalytic materials and methods for preparing the same. Background Art
[0002] Antibiotics are a class of drugs used to kill or inhibit bacteria, with more than a thousand types. In surface water, antibiotics can be divided into six major categories according to their chemical structure and properties: sulfonamides, tetracyclines, β-lactams, macrolides, aminoglycosides and quinolones. These drugs are widely used in human medicine, veterinary medicine and agricultural production. In human medicine, antibiotics are used to treat various bacterial infections and are indispensable drugs in modern medicine. However, in some areas, the abuse of antibiotics is becoming increasingly serious, such as improper use for non-bacterial infections or excessive preventive medication. Sulfonamide antibiotics, especially in animal husbandry, are widely used to treat and prevent bacterial infections in animals, inhibiting their growth and reproduction by blocking bacterial protein synthesis, thereby improving animal health and agricultural production efficiency. Sulfamethoxazole (SMX) is a common sulfonamide antibiotic that is widely used in agriculture. It has a high detection rate and concentration in the environment and is difficult to degrade in the natural environment. SMX is usually discharged into water bodies with farm waste and urban sewage. Traditional sewage treatment processes are difficult to completely remove SMX, resulting in its accumulation in rivers, lakes and groundwater, which in turn pollutes the ecosystem. Studies have shown that the concentration of SMX in the water environment can have toxic effects on microbial metabolic processes, promote the spread of drug-resistant genes, and have negative effects on aquatic plants and animals. Therefore, the development of effective pollution control and remediation technologies is crucial to protecting agricultural water resources, maintaining ecological balance and public health.
[0003] Advanced oxidation technology of activated persulfate is an efficient method for water treatment and pollutant degradation, which is widely used in industrial wastewater and drinking water treatment. This technology uses persulfate as a strong oxidant, which can quickly oxidize and degrade pollutants into harmless substances. It has high reactivity and practical application value. Persulfate has become a research hotspot in the field of wastewater treatment and degradation of emerging organic pollutants due to its low price, stable chemical properties, wide applicable pH range, and easy storage and transportation. Persulfate includes peroxymonosulfate (PMS, HSO5 - ) and peroxydisulfate (PDS, S2O8 2- Among them, PMS has attracted much attention due to its asymmetric molecular structure, which makes it easier to be activated by bond breaking.
[0004] Single Atom Catalysts (SACs) are an important development direction in the field of catalysis in recent years. Their unique properties have attracted widespread attention in catalytic science. The following are some of the main advantages of single atom catalysts and their related details: High atomic utilization: In single atom catalysts, each metal atom is exposed on the catalytic surface and can directly participate in the catalytic reaction. Compared with traditional nanoparticle catalysts, many metal atoms of the latter may be wrapped inside the particles and cannot participate in the catalytic reaction. This structure makes the atomic utilization of single atom catalysts almost 100%, thereby minimizing the consumption of precious metals and optimizing the utilization of resources. High active catalytic performance: In SACs, each single atom can become a catalytic site, thus providing more active centers. This structure makes SACs generally show higher catalytic activity than polyatomic clusters or nanoparticle catalysts because the catalytic reaction is almost involved in the whole process. High selectivity and low occurrence of side reactions: The active sites provided by SACs are evenly distributed, which enables more precise control of the catalytic reaction, thereby improving the selectivity of the product. In some catalytic reactions, this high selectivity can significantly increase the yield of the target product while reducing the formation of by-products. Easy to control: The catalytic performance of single-atom catalysts can be precisely controlled by changing the metal species, support type, and the interaction between the metal and the support. This flexibility allows SACs to be designed as highly targeted catalysts to meet the needs of specific reactions. Low toxicity and environmental friendliness: Due to the high activity and high selectivity of SACs, they are generally able to reduce the generation of toxic byproducts and environmental pollutants. This makes SACs a more environmentally friendly catalytic choice and meets the requirements of green chemistry. Easy separation and recovery: The design of single-atom catalysts usually takes into account the separation and recovery of catalysts, especially in liquid phase reactions. SACs are often designed to be easily separated and recovered from the reaction system, which helps to reduce the cost of the catalyst and improve economic benefits. In general, single-atom catalysts represent a frontier in catalyst research and application with their advantages of high atom utilization, high activity, high selectivity, easy controllability, low toxicity, and easy recovery.
[0005] The mechanism of persulfate activation by single-atom catalysts is generally divided into free radical oxidation (SO4 - ·,·OH and O2 - ·) and non-radical oxidation ( 1 O2, high-valent metal oxides and electron transfer). The free radical mechanism involves the activation of persulfate by a single-atom catalyst (such as iron, copper and other transition metal single atoms) to generate SO4 -· and ·OH. In this process, the single-atom catalyst acts as a central point, and the high concentration of active sites can promote efficient free radical generation, so it has a high activation efficiency. However, the non-specificity of the free radical reaction may lead to a certain degree of by-product generation, and the reaction conditions (such as pH, temperature, etc.) need to be strictly controlled to ensure the efficient progress of the reaction. The non-radical mechanism usually involves the direct electron transfer process of persulfate through a single-atom catalyst without free radical mediation. This mechanism may produce a small amount or no free radicals, and the reaction process occurs in a more controlled and gentle manner. Due to the absence of free radicals, non-target reactions and the formation of by-products can be reduced, and this mechanism may allow the reaction to proceed under milder conditions, reducing the requirements for the reaction system. However, the non-radical mechanism may not be able to effectively remove some pollutants that are difficult to degrade. In general, the non-radical mechanism has better stability than the free radical mechanism and is not easily affected by environmental conditions. The means of verifying the non-radical pathway usually include quenching experiment inference, electron paramagnetic resonance (EPR) technology, various electrochemical experiments, and degradation of different types of pollutants. Summary of the invention
[0006] The present invention belongs to the field of single-atom catalysis technology, and in particular relates to a Co2TA catalyst that can efficiently catalyze the degradation of sulfamethoxazole. 0.5 Single atom catalytic material and preparation method thereof. The single atom catalyst Co2TA 0.5 It has a wide pH range, can maintain good performance at various temperatures, is suitable for various water bodies, has strong anti-interference ability, and can be reused.
[0007] The present invention adopts the following technical solution to solve the above technical problems: a Co2TA catalyst capable of efficiently catalyzing the degradation of sulfamethoxazole 0.5 Single atom catalytic material and preparation method thereof, the specific steps are:
[0008] (1) Disperse 2 mmol of cobalt chloride hexahydrate, 0.5 g of tannic acid (TA), 5 g of melamine (MA), and 5 g of cyanuric acid (CA) in 400 mL of water and stir magnetically at room temperature overnight;
[0009] (2) After removing the supernatant from the solution in step (1), the mixture was dried in a 60° C. forced air drying oven overnight and then ground with an agate mortar;
[0010] (3) Annealing in a nitrogen tube furnace at 600°C for 2 h, nitrogen flow rate 60, heating time: 5°C / min, 600°C maintained for 2 h;
[0011] (4) The prepared black carbon was ground with an agate mortar and then washed with a 0.5 M sulfuric acid solution at room temperature for 12 h, and then filtered and washed with water until the filtrate was nearly neutral in pH;
[0012] (5) Finally, the product was dried in a vacuum oven at 60°C, ground with an agate mortar and packed into a tube to obtain Co2TA 0.5 catalyst.
[0013] Preferably, in step (1), the magnetic stirring speed is 600 rpm at room temperature for 12 h.
[0014] Preferably, the 0.5 M sulfuric acid solution in step (4) is prepared by adding 13.6 ml of concentrated sulfuric acid to 486.4 ml of water.
[0015] Preferably, the stirring speed in step (4) is 600 rpm.
[0016] Preferably, the filter membrane used for suction filtration and washing in step (4) is a 0.22 um filter membrane.
[0017] The present invention adopts another technical solution to solve the above technical problems. The Co2TA 0.5 Preparation method of catalytic material Co2TA 0.5 catalyst.
[0018] The present invention adopts another technical solution to solve the above technical problems. The Co2TA 0.5 Application of catalyst, the Co2TA 0.5 The catalytic material is used to activate potassium peroxymonosulfate to degrade sulfamethoxazole SMX.
[0019] Preferably, 0.1 g L -1 Co2TA 0.5 The catalytic material was activated by 0.4 mM PMS potassium peroxymonosulfate, and the degradation rate of 10 mg / L SMX sulfamethoxazole reached 100% within 30 min.
[0020] The amount of cobalt chloride hexahydrate and tannic acid was adjusted. The material named Co1TA0 was prepared by using 1mM cobalt chloride hexahydrate and 0g tannic acid. The same method was used to change the amount of the two to prepare Co1TA 0. 、Co1TA 0.25 、Co1TA 0.5 、Co1T 01 、Co1TA2、Co0TA 0.5 、Co 0.5 TA 0.5 、Co1TA 0.5 、Co2TA 0.5 、Co3TA 0.5 .
[0021] The dosages of cobalt chloride hexahydrate and tannic acid were 2 mM and 0.5 g, respectively, and the obtained Co2TA 0.5 Single-atom catalysts perform best.
[0022] Beneficial effects of the present invention:
[0023] The present invention adopts a simple and feasible preparation method to prepare Co2TA which can efficiently degrade the toxic persistent organic matter SMX. 0.5 The single-atom catalyst has the characteristics of being able to efficiently degrade the toxic persistent organic compound SMX at room temperature and pressure; and provides a method for obtaining the single-atom catalyst material through a simple and green preparation process.
[0024] In the experiment of changing the amount of TA while keeping the amount of Co, it was found that during the degradation of SMX by the catalyst, the degradation performance of Co1TA2 was the worst, and it could only degrade 68.5% of SMX within 60 minutes, while Co1TA 0.5 SMX can be 100% degraded in 60 min. Then the amount of Co is changed while the amount of TA is maintained. It is found that Co0TA 0.5 The single-atom catalyst could only degrade 26.8% of SMX, while Co2TA 0.5 It can degrade SMX by 100% within 30 minutes. 0.5 Single-atom catalysts are the single-atom catalysts with the best performance.
[0025] The same synthesis method as in Example 1 was used to change the metal to prepare four single-atom catalysts: iron, nickel, manganese, and copper. A 10 mg / L SMX aqueous solution was prepared with deionized water. 30 ml was taken and placed in a 50 ml jacketed beaker. 0.1 g L -1 Prepared Co2TA 0.5 、Fe2TA 0.5 、Mn2TA 0.5 、Ni2TA 0.5 、Cu2TA 0.5 The single atom catalyst and 0.4 mM PMS, as well as PMS alone, were added. The reaction temperature was controlled to be 25 °C with condensation water. The reaction was carried out under stirring. The concentration of SMX before and after the reaction was determined by high performance liquid chromatography. The results are as follows: Fig.10 As shown, Cu2TA 0.5 The single atom catalyst can remove 26.8% of SMX and Ni2TA in 60 min. 0.5 The single atom catalyst can remove 42.5% of SMX and Mn2TA in 60 min. 0.5 The single atom catalyst can remove 70.8% of SMX in 60 min, PMS alone can only remove 21.8% of SMX, and Co2TA0.5 The single atom catalyst can remove 100% of SMX in 30 min.
[0026] The single-atom catalyst Co2TA 0.5 It has a wide pH range, can maintain good performance at various temperatures, is suitable for various water bodies, has strong anti-interference ability, and can be reused. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the XRD pattern of the single atom catalyst prepared in Example 1 of the present invention;
[0028] Figure 2 It is a series of effect diagrams of the catalyst degradation of SMX prepared in Example 1;
[0029] Figure 3 Example 2 Co2TA under different quenchers 0.5 Effect diagram of single atom degradation of SMX;
[0030] Figure 4 The reactive species detected by EPR in Example 2 is singlet oxygen;
[0031] Figure 5 Example 3 Co2TA under different anions 0.5 Effect diagram of single atom degradation of SMX;
[0032] Figure 6 This is the recycling experiment Co2TA of Example 4 0.5 Effect diagram of single atom degradation of SMX;
[0033] Figure 7 Example 5 Co2TA at different pH 0.5 Effect diagram of single atom degradation of SMX;
[0034] Figure 8 Example 6 Co2TA at different temperatures 0.5 Effect diagram of single atom degradation of SMX;
[0035] Fig. 9 Example 7 Co2TA in different water bodies 0.5 Effect diagram of single atom degradation of SMX;
[0036] Fig.10 This is a diagram showing the effect of synthesizing different metals and PMS alone in the degradation of SMX in Example 8; DETAILED DESCRIPTION
[0037] Embodiment 1:
[0038] Co2TA0.5 Preparation of single-atom catalysts
[0039] (1) 2 mmol of cobalt chloride hexahydrate, 0.5 g of tannic acid (TA), 5 g of melamine (MA), and 5 g of cyanuric acid (CA) were dispersed in 400 mL of water and magnetically stirred at room temperature overnight (12 h, rotation speed 600 rpm).
[0040] (2) After removing the supernatant from the solution in step (1), the solution was dried in a 60° C. forced air drying oven overnight and then ground with an agate mortar.
[0041] (3) Annealing reaction was carried out in a nitrogen tube furnace at 600°C for 2 h (nitrogen flow rate: 60, heating time: 5°C / min, 600°C maintained for 2 h).
[0042] (4) The prepared black carbon was ground with an agate mortar and then washed with 0.5 M sulfuric acid solution (13.6 ml of concentrated sulfuric acid + 486.4 ml of water) at room temperature for 12 h (speed 600 rpm), and then filtered and washed with water (0.22 um filter membrane) until the filtrate was nearly neutral in pH.
[0043] (5) Finally, the product was dried in a vacuum oven at 60°C, ground with an agate mortar and packed into a tube to obtain Co2TA 0.5 catalyst.
[0044] The amount of cobalt chloride hexahydrate and tannic acid was adjusted. The material named Co1TA0 was prepared by using 1mmol-3mmol of cobalt chloride hexahydrate and 0g-2g of tannic acid. The same method was used to change the amount of the two to prepare Co1TA0, Co1TA 0.25 、Co1TA 0.5 、Co1TA1、Co1TA2、Co0TA 0.5 、Co 0.5 TA 0.5 、Co1TA 0.5 、Co2TA 0.5 、Co3TA 0.5 .
[0045] like Figure 1 The X-ray diffraction (XRD) spectrum shows the typical structural characteristics of the polymer CN framework, and the diffraction peak at 27.5° is attributed to the layer stacking structure in the (001) direction with an interlayer spacing of 0.33 nm, indicating that this series of materials was successfully prepared.
[0046] Prepare a 10 mg / L SMX aqueous solution with deionized water, take 30 ml and put it into a 50 ml jacketed beaker, then add 0.1 g L -1 Prepared Co2TA 0.5The single atom catalyst and 0.4 mM PMS were added, and the reaction temperature was controlled to 25 °C with condensed water. The reaction was carried out under stirring. The concentration of SMX before and after the reaction was determined by high performance liquid chromatography. The results are as follows: Figure 2 As shown, under the same catalytic degradation conditions, the Co2TA prepared in this experiment 0.5 Single atom catalysts exhibit excellent catalytic performance in the degradation of SMX.
[0047] In the experiment of maintaining the amount of Co and changing the amount of TA, it was found that during the process of catalyst degradation of SMX, Co1TA0 could degrade 100% of SMX within 60 minutes, and Co1TA 0.25 100% of SMX and Co1TA can be degraded within 60 minutes 0.5 In 60 min, 100% of SMX can be degraded by Co1TA1. Co1TA2 has the worst degradation performance, which can only degrade 68.5% of SMX in 60 min. 0.5 Compared with other materials, the degradation performance is better. Then the amount of TA is kept and the amount of Co is changed. Co0TA 0.5 Only 26.8% of SMX and Co could be degraded within 60 min. 0.5 TA 0.5 83.5% of SMX and Co1TA can be degraded within 60 minutes 0.5 100% SMX and Co3TA can be degraded within 60 minutes 0.5 100% of SMX can be degraded within 60 min, while Co2TA 0.5 It can degrade SMX by 100% within 30 minutes. Therefore, it can be considered that Co2TA 0.5 Single atom catalysts are the best performing single atom catalysts in this series of materials.
[0048] Embodiment 2:
[0049] Prepare a 10 mg / L SMX aqueous solution with deionized water, take 30 ml and put it into a 50 ml jacketed beaker, first add L-histidine, methanol, tert-butyl alcohol, tetramethylpiperidinoxide into different jacketed beakers, then add 0.1 g L -1 The prepared single atom catalyst and 0.4 mM PMS were added, the condensing water was turned on to control the reaction temperature to 25 °C, and the reaction was carried out under stirring. The concentration of SMX before and after the reaction was determined by high performance liquid chromatography technology, such as Figure 3As shown in Figure 2, the addition of L-histidine reduced the original degradation rate by 60%, and the addition of MeOH also reduced its degradation rate by about 5%, while the addition of TBA had no effect on the degradation effect, indicating that the hydroxyl radicals did not play a role. In summary, the cobalt atoms in the catalyst activated the PMS to produce 1 O2 and SO4 - Involved in the degradation of sulfamethoxazole, 1 O2 is the main active substance.
[0050] In addition, this experiment used EPR detection 1 The characteristic signal generated by the combination of O2 and the spin trap (TEMP) can further be used to generate the Co2TA 0.5 Activate PMS production 1 O2 provides strong evidence. Figure 4 As shown, Co2TA 0.5 In the activated PMS system, not only 1 The presence of O2, and as time goes by, 1 The signal peak of O2 becomes weaker and weaker, which may be due to the reaction process 1 O2 participates in the reaction and gradually decreases.
[0051] Embodiment 3:
[0052] Prepare a 10 mg / L SMX aqueous solution with deionized water, take 30 ml and put it into a 50 ml jacketed beaker. First, add 1 mM chloride ions, hydrogen phosphate ions, bicarbonate ions, and nitrate ions to different jacketed beakers, and then add 0.1 g L -1 Prepared Co2TA 0.5 The single atom catalyst and 0.4 mM PMS were added, and the reaction temperature was controlled to 25 °C with condensed water. The reaction was carried out under stirring. The concentration of SMX before and after the reaction was determined by high performance liquid chromatography. The results are as follows: Figure 5 As shown, under different anion background environments, Co2TA 0.5 Single atom catalysts exhibit excellent catalytic performance in the degradation of SMX.
[0053] Embodiment 4:
[0054] Co2TA 0.5 The single-atom catalyst material has the advantages of excellent reusability and recyclability. The solution after the reaction can be filtered through a 0.22μm filter membrane and then vacuum dried for reuse. Figure 6 As shown, Co2TA 0.5The decrease in degradation ability after 4 cycles may be due to the cumulative adsorption of degradation products in the pores that mask the active sites, resulting in a decrease in activation ability. 0.5 The catalytic degradation performance was completely restored.
[0055] Embodiment 5:
[0056] Prepare a 10 mg / L SMX aqueous solution with deionized water, take 30 ml and put it into a 50 ml jacketed beaker, adjust the pH of the reaction solution to 3, 5, 7, and 10 respectively, and then add 0.1 g L -1 Prepared Co2TA 0.5 The single atom catalyst and 0.4 mM PMS were added, and the reaction temperature was controlled to 25 °C with condensed water. The reaction was carried out under stirring. The concentration of SMX before and after the reaction was determined by high performance liquid chromatography. The results are as follows: Figure 7 As shown, under different pH conditions, Co2TA 0.5 The catalytic degradation performance of the materials can be maintained well.
[0057] Embodiment 6:
[0058] Prepare a 10 mg / L SMX aqueous solution with deionized water, take 30 ml and put it into a 50 ml jacketed beaker. First adjust the temperature of the reaction solution to 25, 35, 45, and 55 °C, then add 0.1 g L -1 Prepared Co2TA 0.5 The single atom catalyst and 0.4 mM PMS were added, and the reaction temperature was controlled to 25 °C with condensed water. The reaction was carried out under stirring. The concentration of SMX before and after the reaction was determined by high performance liquid chromatography. The results are as follows: Figure 8 As shown, under different temperature conditions, Co2TA 0.5 The catalytic degradation performance of the materials can be maintained well.
[0059] Embodiment 7:
[0060] Different water bodies were used to simulate different water environments in the natural state. Deionized water, tap water, secondary effluent from a sewage treatment plant, Longzi Lake water, and Nanhu Lake water were used to prepare a 10 mg / L SMX aqueous solution. 30 ml was placed in a 50 ml jacketed beaker, and 0.1 g L -1 Prepared Co2TA 0.5 The single atom catalyst and 0.4 mM PMS were added, and the reaction temperature was controlled to 25 °C with condensed water. The reaction was carried out under stirring. The concentration of SMX before and after the reaction was determined by high performance liquid chromatography. The results are as follows: Fig. 9 As shown in the figure, under different water environments, Co2TA 0.5The catalytic degradation performance of the materials can be maintained well, which indicates that the materials can be used to remove pollutants in real water environments.
[0061] Example 8
[0062] The preparation method is the same as that in Example 1, except that cobalt chloride hexahydrate is replaced by ferric chloride hexahydrate, manganese chloride tetrahydrate, nickel chloride hexahydrate, and cupric chloride dihydrate to obtain Fe2TA 0.5 、Mn2TA 0.5 、Ni2TA 0.5 、Cu2TA 0.5 Single atom catalyst, prepare a 10 mg / L SMX aqueous solution with deionized water, take 30 ml and put it into a 50 ml jacketed beaker, add 0.1 g L -1 Prepared Co2TA 0.5 、Fe2TA 0.5 、Mn2TA 0.5 、Ni2TA 0.5 、Cu2TA 0.5 The single atom catalyst and 0.4 mM PMS, as well as PMS alone, were added. The reaction temperature was controlled to be 25 °C with condensation water. The reaction was carried out under stirring. The concentration of SMX before and after the reaction was determined by high performance liquid chromatography. The results are as follows: Fig.10 As shown, Cu2TA 0.5 The single atom catalyst can remove 26.8% of SMX and Ni2TA in 60 min. 0.5 The single atom catalyst can remove 42.5% of SMX and Mn2TA in 60 min. 0.5 The single atom catalyst can remove 70.8% of SMX in 60 min, PMS alone can only remove 21.8% of SMX, and Co2TA 0.5 The single atom catalyst can remove 100% of SMX in 30 min.
[0063] In summary, Co2TA 0.5 Single-atom catalysts have excellent anti-interference ability and are recyclable.
[0064] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.
Claims
1. A Co2TA for the degradation of sulfamethoxazole SMX 0.5 The method for preparing a catalytic material is characterized by: The specific steps are: (1) Disperse 2 mmol of cobalt chloride hexahydrate, 0.5 g of tannic acid (TA), 5 g of melamine (MA), and 5 g of cyanuric acid (CA) in 400 mL of water and stir magnetically at room temperature overnight; (2) After removing the supernatant from the solution in step (1), the mixture was dried in a 60° C. forced air drying oven overnight and then ground with an agate mortar; (3) Annealing in a nitrogen tube furnace at 600°C for 2 h, nitrogen flow rate 60, heating time: 5°C / min, 600°C maintained for 2 h; (4) The prepared black carbon was ground with an agate mortar and then washed with a 0.5 M sulfuric acid solution at room temperature for 12 h, and then filtered and washed with water until the filtrate was nearly neutral in pH; (5) Finally, the product was dried in a vacuum oven at 60°C, ground with an agate mortar and packed into a tube to obtain Co2TA 0.5 catalyst.
2. Co2TA for degrading sulfamethoxazole SMX according to claim 1 0.5 The method for preparing a catalytic material is characterized by: In step (1), the magnetic stirring speed is 600 rpm at room temperature for 12 h.
3. Co2TA for degrading sulfamethoxazole SMX according to claim 1 0.5 The method for preparing a catalytic material is characterized by: In step (4), the 0.5 M sulfuric acid solution is prepared by adding 13.6 ml of concentrated sulfuric acid to 486.4 ml of water.
4. Co2TA for degrading sulfamethoxazole SMX according to claim 1 0.5 The method for preparing a catalytic material is characterized by: The stirring speed in step (4) is 600 rpm.
5. Co2TA for degrading sulfamethoxazole SMX according to claim 1 0.5 The method for preparing a catalytic material is characterized by: The filter membrane used for suction filtration and washing in step (4) is a 0.22 um filter membrane.
6. Co2TA according to any one of claims 1 to 5 0.5 Preparation method of catalytic material Co2TA 0.5 catalyst.
7. The Co2TA according to claim 6 0.5 The application of the catalyst is characterized by: The Co2TA 0.5 The catalytic material is used to activate potassium peroxymonosulfate to degrade sulfamethoxazole SMX.
8. The Co2TA according to claim 7 0.5 The application of the catalyst is characterized by: Using 0.1 g L -1 Co2TA 0.5 The catalytic material was activated with 0.4 mM potassium permonosulfate PMS, and the degradation rate of 10 mg / L sulfamethoxazole SMX reached 100% within 30 min.
Citation Information
Cited By
Method for degrading chlorophenol organic pollutants in water by activating persulfate with cobalt-cerium dioxide monatomic catalyst in presence of bicarbonate radical
CN120681868A
